Reducing impact loading in runners: A one-year follow-up - Bowser, B. J.; Fellin, R.; Milner, C. E.; Pohl, M. B.; Davis, I. S. (Medicine & Science in Sports & Exercise, 2018)
Increased vertical impact loading during running has been associated with a variety of running related injuries including stress fractures, patellofemoral pain, and plantar fasciitis.